Modeling, Simulation, and Operations Analysis in Afghanistan and Iraq Operational Vignettes, Lessons Learned, and a Survey of Selected Efforts - Connable, Ben (RAND Corporation, 2014)
RAND researchers conducted a lessons learned examination of operations analysis, modeling, and simulation in support of Operation Enduring Freedom and Operation Iraqi Freedom. Researchers identified ways in which analysts have attempted to support commanders' decisionmaking and describe a selection of the models and tools they employed.